2009
DOI: 10.1007/s10603-009-9110-0
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Health Claims Among Nordic Consumers

Abstract: Health claims, Healthy eating, Marketing, Food,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 31 publications
3
40
0
6
Order By: Relevance
“…The same reasoning is valid for the country of residence, for which our results confirm the literature that reports that the differences between countries represents a valid predictor of the choice of health claims (Saba et al, 2010;Van Trijp & Van der Lans, 2007). In particular, our results show a lower GHI and a lack of trust in health claims among the Danish consumers, which can be related to this country's recent market exposure to health claims (Grunert et al, 2009;Lähteenmäki et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The same reasoning is valid for the country of residence, for which our results confirm the literature that reports that the differences between countries represents a valid predictor of the choice of health claims (Saba et al, 2010;Van Trijp & Van der Lans, 2007). In particular, our results show a lower GHI and a lack of trust in health claims among the Danish consumers, which can be related to this country's recent market exposure to health claims (Grunert et al, 2009;Lähteenmäki et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…In the ambit of socio-demographic characteristics, the most significant predictor proves to be the country of residence (Saba et al, 2010;Van Trijp & Van der Lans, 2007). The literature interprets this phenomenon by associating it to various factors of the sociocultural environment, such as market exposure to health claims, trust in authorities, and familiarity with the carrier and the ingredient (Annunziata & Vecchio, 2011;Grunert et al, 2009;Saba et al, 2010). Conflicting results are recorded for gender, in relation to which several authors find a greater interest among women, while others observe no significant differences between the sexes (Ares & Gámbaro, 2007;Dean et al, 2007;Urala, Arvola, & Lähteenmäki, 2003;Urala & Lähteenmäki, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As general health claims tend to be shorter (28) , easier to understand and evoke positive associations from memory (29) , they may be more likely to be preferred by consumers (4,26) . This might explain why some studies reported disease risk reduction claims to be perceived as less credible and less attractive than general health claims, as was the case for Belgian (22) , Irish (27) and Nordic (30) consumers. Differences across countries as to which health claim format is preferred have been reported.…”
Section: Health Claim Formatmentioning
confidence: 99%
“…Claims were constructed by combining different base products (bread, pork and yoghurt) with different active ingredients (no ingredient, omega-3-familiar and bioactive peptidesunfamiliar), type of benefit (cardiovascular, memory function and weight management) and claim structure (function only, health outcome only, ingredient + function, ingredient + health outcome, function + health outcome and ingredient + function + health outcome). The claims were framed either positively (achieving something positive) or negatively (avoiding something negative) and with/without the use of the qualifier 'may' (39,40) . An example of a claim used would be: 'This bread contains omega-3 which enhances memory function and therefore increases the likelihood of good memory retention'.…”
Section: Nordic Studymentioning
confidence: 99%